The nature of post-occupancy modifications of selected low-income housing estates in Nigeria - Miriam Ijeoma Chukwuma-Uchegbu; Muhammad Saidu Aliero (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2022)
This paper aims to evaluate the nature of post-occupancy modifications of selected income housing estates in Nigeria. The research adopts both the quantitative and qualitative approaches and is essentially survey-based. Therefore, the research population is all housing units of low-income public housing estates in Owerri Metropolis. A simple random technique was further adopted to select five low-income housing estates within the low-income group for this study. Participants of this study were further sampled and selected based on the following requirements and eligibility criteria - they must be residents in the residential estates under study; they must be household heads (or their representatives) of the buildings in the selected housing estates and the building must have been in existence for over ten years (which is enough time for modification to have taken place). The data were collected through the use of a structured questionnaire and field observations, and analysis of this data relied on the computer-based statistical software called STATA 13.0. Results were presented and discussed, pinpointing the nature of post-occupancy modifications in the five selected low-income housing estates. The results further show various kinds of modifications (addition of rooms, alteration of site arrangement, alteration of fence design, alteration of roofing pattern, addition of shop spaces, change of use, and outright total modification) have taken place across the five housing estates studied.